Regression analysis for the social sciences - Gordon, Rachel A. (Routledge, Taylor & Francis Group, 2015)
"This book provides graduate students in the social sciences with the basic skills that they need in order to estimate, interpret, present, and publish basic regression models using contemporary standards. Key features of the book include: - interweaving the teaching of statistical concepts with examples developed for the course from publicly available social science data or drawn from the literature; - thorough integration of teaching statistical theory with teaching data processing and analysis using Stata; - use of chapter exercises in which students practice programming and interpretation on the same data set and course exercises in which students can choose their own research questions and data set"--Resumé vydavatele